Marein Ameliorates Myocardial Fibrosis by Inhibiting HIF-1α and TGF-β1/Smad2/3 Signaling Pathway in Isoproterenol-stimulated Mice and TGF-β1-stimulated Cardiac Fibroblasts - Niu, Guanghao; Zhao, Ying; Song, Huafeng; Song, Quan; Yin, Xiaoyun; Zhu, Zengyan; Xu, Junchi (Current Pharmaceutical Design, 2024)
Background: Myocardial fibrosis significantly contributes to the pathogenesis and progression of heart failure. Objective: We probe into the impact of marein, a key bioactive compound in functional food Coreopsis tinctoria, on isoproterenol-stimulated myocardial fibrotic mice and transforming growth factor β1 (TGF-β1)-stimulated cardiac fibroblasts (CFs). Methods: Isoproterenol was administered to the experimental mice via subcutaneous injection, and simultaneous administration of marein (25-100 mg/kg) was performed via oral gavage. CFs were stimulated with TGF- β1 to trigger differentiation and collagen synthesis, followed by treatment with marein at concentrations of 5-20 μM. Results: Treatment with marein in mice and CFs resulted in a significant reduction in the protein expression levels of α-smooth muscle actin, collagen type I, and collagen type III. Additionally, marein treatment decreased the protein expression levels of TGF-β1, hypoxia-inducible factor-1α (HIF-1α), p-Smad2/3, and Smad2/3. Notably, molecular docking analysis revealed that marein directly targets HIF-1α. Conclusion: Marein might exert a protective function in isoproterenol-stimulated myocardial fibrotic mice and TGF-β1-stimulated CFs, which might result from the reduction of TGF-β1 induced HIF-1α expression, then inhibiting p-Smad2/3 and Smad2/3 expressions.
Keywords: HIF-1α